Analysis of the Influence of Content Quality, Influencer Credibility, and E-WOM on Influencer-Follower Trust on Digital Investment Platforms - Hery Purnomo; Vivid Violin; Riesna Apramilda; Fahrina Mustafa; Sonya Sidjabat; Ratu Nadya Wahyuningratna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to evaluate the extent to which content quality, influencer credibility, and electronic word of mouth (E-WOM) influence followers' trust levels in influencers on digital investment platforms. A quantitative approach was used in this study, with data collected through a survey involving 300 respondents. Respondents were selected purposively based on certain criteria: active users of digital investment platforms for at least six months, following influencers who discuss investment topics, and actively accessing investment-related content in the past three months. The analysis method used multiple linear regression analysis. The results of the analysis indicate that, partially and simultaneously, the variables of content quality, influencer credibility, and E-WOM have a significant influence on follower trust. These findings provide an important contribution to the development of theory in the field of digital marketing, particularly regarding consumer behavior in the context of digital investment. They also offer practical recommendations for industry players to design effective, honest, and user-experience-focused communication strategies.